Implicações de plantas de cobertura e de doses de nitrogênio no rendimento de grãos da soja - Silveira, Lucas da (2018)
The beneficial effects to the soil, when using cover crops, are numerous, such as nutrient cycling, nitrogen fixation, pest and disease cycle breakdown, soil structuring and dry matter addition. This makes the subsequent crop better able to express its productive potential. The macronutrient nitrogen is a key element for any plant, especially in the early stages of crop development. The objective of the present work was to evaluate the effect of forage pea (Pisum sativum L.) and black oats (Avena strigosa) and nitrogen rates on soybean yield. Two soil physical properties were evaluated: soil density, total porosity, microporosity and macroporosity, and in the soybean crop were evaluated the production components: height, mass of one hundred grains and grain yield of the soil. soybean (Glycine max). The experiments were conducted in the experimental area of the Agronomic Institute of Paraná - IAPAR, regional pole of Santa Tereza do Oeste. The soil of the region is classified as a Typical Dystrophic Red Latosol. The experimental design was a randomized complete block design with five replications. The plots consisted of winter cover crops, forage peas and black oats, and the subplots of nitrogen doses: 0, 25, 50, 75 and 100 kg ha-1 applied in a hedge without incorporation using the urea, at 20 days after emergence, when the plants were in stage V3. The area of each experimental unit consisted of nine soybean lines per 5.1 m length, spacing 0.45 m between them. The data were submitted to analysis of variance, in which, for the quantitative factors, the regression analysis was performed and, for the qualitative characteristics, the Tukey test (p <0.05) was performed. By the addition of mineral nitrogen in the soil, it was observed that there was no gain of production in the soybean crop, with this it can be said that in well structured Latosols and with high fertility, only the nitrogen present in the organic matter of the soil is sufficient for supply the demand for this element by the soybean crop.